Is there a role for bradykinin in cerebral malaria pathogenesis? - Pinheiro, Alessandro de Sa; Kazura, James W.; Pinheiro, Ana Acacia; Schmaier, Alvin H. (Frontiers in Cellular and Infection Microbiology, 2023)
Malaria is a parasitic disease of global health significance and a leading cause of death in children living in endemic regions. Although various Plasmodium species are responsible for the disease, Plasmodium falciparum infection accounts for most severe cases of the disease in humans. The mechanisms of cerebral malaria pathogenesis have been studied extensively in humans and animal malaria models; however, it is far from being fully understood. Recent discoveries indicate a potential role of bradykinin and the kallikrein kinin system in the pathogenesis of cerebral malaria. The aim of this review is to highlight how bradykinin is formed in cerebral malaria and how it may impact cerebral blood-brain barrier function. Areas of interest in this context include Plasmodium parasite enzymes that directly generate bradykinin from plasma protein precursors, cytoadhesion of P. falciparum infected red blood cells to brain endothelial cells, and endothelial cell blood-brain barrier disruption.